2004
DOI: 10.1577/03-044
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Multipass Electrofishing for Estimating the Abundance of Stream-Dwelling Salmonids

Abstract: Failure to estimate capture efficiency, defined as the probability of capturing individual fish, can introduce a systematic error or bias into estimates of fish abundance. We evaluated the efficacy of multipass electrofishing removal methods for estimating fish abundance by comparing estimates of capture efficiency from multipass removal estimates to capture efficiencies measured by the recapture of known numbers of marked individuals for bull trout Salvelinus confluentus and westslope cutthroat trout Oncorhyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
311
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(340 citation statements)
references
References 34 publications
20
311
9
Order By: Relevance
“…Previous studies (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005) have demonstrated that electrofishing removals can produce biased estimates of abundance because CP is lower than what is actually measured, producing abundance estimates that are too low, and in our case, removal efficiency estimates that were probably too high. We have no way of knowing true CP in this study.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Previous studies (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005) have demonstrated that electrofishing removals can produce biased estimates of abundance because CP is lower than what is actually measured, producing abundance estimates that are too low, and in our case, removal efficiency estimates that were probably too high. We have no way of knowing true CP in this study.…”
mentioning
confidence: 51%
“…Although CP from multipass removals averaged 0.78, we realized that this was probably an overestimate (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005), which would in turn cause underestimation of population abundance and overestimation of removal efficiency (especially for age-0 fish). Estimates of abundance should therefore be considered minimum estimates, and estimates of CP and removal efficiency should be considered maximum estimates.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Habitat size and complexity, fish species and size, density, and the intensity of sampling effort may affect the efficiency of snorkeling estimates of fish abundance (Riley and Fausch 1992, Rodgers et al 1992, Bayley and Dowling 1993, Peterson et al 2004). .…”
Section: Reach-scale Habitat Associationsmentioning
confidence: 99%
“…Removal estimates generally do not account for heterogeneity in capture probability, which can lead to an underestimate in population size (Peterson et al 2004). This underestimate in population size could lead to exaggerated effects of flathead catfish predation on native fish functional groups and imprecise or inaccurate predictions of possible management actions related to flathead catfish removal programs.…”
Section: Model Limitationsmentioning
confidence: 99%